Curt Flood in the media baseball, race, and the demise of the activist-athlete - Khan, Abraham Iqbal (Jackson : University Press of Mississippi, 2012)
Curt Flood in the Media examines the public discourse surrounding Curt Flood (1938-1997), the star center fielder for the St. Louis Cardinals throughout the sixties. In 1969, Flood was traded to the Philadelphia Phillies. At the time, all Major League Baseball players were subject to the reserve clause, which essentially bound a player to work in perpetuity for his original team, unless traded for another player or sold for cash, in which case he worked under the same reserve conditions for the next team.Flood refused the trade on a matter of principle, arguing that Major League Baseball had v
Cover; Contents; Acknowledgments; 1. Curt Flood and the Demise of the Activist-Athlete; 2. Curt Flood's Public Case; 3. Jackie Robinson and the Rhetoric of the Black Press; 4. The Disappearance of Curt Flood's Blackness; 5. Race, Slavery, and the Revolt of the Black Athlete; 6. Race and Memory in Sport's Public Sphere; Notes; Bibliography; Index; A; B; C; D; E; F; G; H; J; K; L; M; N; O; P; Q; R; S; T; W; X; Y
Description based upon print version of record.
English
Includes bibliographical references and index.
Description based on publisher supplied metadata and other sources.
Keywords: African American baseball players -- Biography; Baseball -- Law and legislation -- United States; Discrimination in sports -- United States; Free agents (Sports) -- United States; Flood, Curt, -- 1938-1997.; Flood, Curt, -- 1938-1997 -- Trials, litigation, etc